Sakralitas Burung Manguni Dalam Teologi Kontekstual Orang (Tou) Minahasa - Alon Mandimpu Nainggolan; Juanda Manullang; Nency Aprilia Heydemans (PASCA : Jurnal Teologi dan Pendidikan Agama Kristen, 2022)
This article aims to describe the culture of the Minahasa (Tou) people about the sacredness of the Manguni bird. The Manguni bird is believed to be a sacred bird initially originating from Minahasa, North Sulawesi. The identity of the Manguni bird by Tou Minahasa is known as the Ot bird or Tototic bird. The Manguni bird for Tou Minahasa has a sacred symbol. Therefore, Tou Minahasa made this bird sacred. The community's attitude to describing the Manguni bird in contextual theology is found in the symbols of the Evangelical Christian Church in Minahasa (GMIM), Minahasa regional symbols/symbols, carvings, and typical Minahasa batik clothes. Tou Minahasa believes that the Manguni bird is an intermediary between humans and God Almighty (Opo Empung Wailan Wangko) and is the bearer of news. This research is influenced by the customs and culture of the Tou Minahasa, which functions to recognize the beliefs of the ancestors (ancestors) that contain noble values. This article uses qualitative methods through observation, in-depth interviews, and literature study. The results of this study concluded that the Manguni bird, both physically and in Minahasa culture, contains sacred values and becomes the identity of Tou Minahasa.